Zebrafish for Personalized Regenerative Medicine; A More Predictive Humanized Model of Endocrine Disease - Arjmand, Babak; Tayanloo-Beik, Akram; Foroughi Heravani, Najmeh; Alaei, Setareh; Payab, Moloud; Alavi-Moghadam, Sepideh; Goodarzi, Parisa; Gholami, Mahdi; Larijani, Bagher (Frontiers in Endocrinology, 2020)
Regenerative medicine is a multidisciplinary field that aims to determine different factors and develop various methods to regenerate impaired tissues, organs, and cells in the disease and impairment conditions. When treatment procedures are specified according to the individual's information, the leading role of personalized regenerative medicine will be revealed in developing more effective therapies. In this concept, endocrine disorders can be considered as potential candidates for regenerative medicine application. Diabetes mellitus as a worldwide prevalent endocrine disease causes different damages such as blood vessel damages, pancreatic damages, and impaired wound healing. Therefore, a global effort has been devoted to diabetes mellitus investigations. Hereupon, the preclinical study is a fundamental step. Up to now, several species of animals have been modeled to identify the mechanism of multiple diseases. However, more recent researches have been demonstrated that animal models with the ability of tissue regeneration are more suitable choices for regenerative medicine studies in endocrine disorders, typically diabetes mellitus. Accordingly, zebrafish has been introduced as a model that possesses the capacity to regenerate different organs and tissues. Especially, fine regeneration in zebrafish has been broadly investigated in the regenerative medicine field. In addition, zebrafish is a suitable model for studying a variety of different situations. For instance, it has been used for developmental studies because of the special characteristics of its larva. In this review, we discuss the features of zebrafish that make it a desirable animal model, the advantages of zebrafish and recent research that shows zebra fish is a promising animal model for personalized regenerative diseases. Ultimately, we conclude that as a newly introduced model, zebrafish can have a leading role in regeneration studies of endocrine diseases and provide a good perception of underlying mechanisms.